A focus on recovery: using the Mental Health Recovery Star as an outcome measure. (2nd January 2016) - Lloyd, Chris; Williams, Philip Lee; Machingura, Tawanda; Tse, Samson
Abstract : Purpose: The Mental Health Recovery Star was adopted as a routine outcome measure by recovery clinicians in the newly developed Mental Health Recovery Service in Queensland, Australia. Design/approach: All service users referred to the Recovery Service during a three-month period completed the Mental Health Recovery Star. A chart audit was conducted to review the utility of the Mental Health Recovery Star as a clinical outcome measure. Findings: Recovery goals identified by service users through this process and the progress they made are reported. Service users identified that they needed assistance in work, social networks, managing mental health and identity and self-esteem. Conclusion: Overall, it was found that the Mental Health Recovery Star was useful in service mapping and assisting recovery clinicians to identify areas that they needed to focus on when providing treatment and following service user's progress. It complemented other outcome measures used by the service.